2017
DOI: 10.1111/lang.12265
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Audiovisual Speech in the Early Stages of Lexical Processing as Revealed by the ERP Word Repetition Effect

Abstract: Numerous studies suggest that audiovisual speech influences lexical processing. However, it is not clear which stages of lexical processing are modulated by audiovisual speech. In this study, we examined the time course of the access to word representations in long‐term memory when they were presented in auditory‐only and audiovisual modalities. We exploited the effect of the prior access to a word on the subsequent access to that word known as the word repetition effect. Using event‐related potentials, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…However, Basirat et al (2018) found that this repetition effect on the P200 interacted with multisensory context. For the initial word presentation, audio-visual words were associated with a smaller ERP than were the audio-only words, suggesting that the visual context facilitated lexical access (see Basirat et al, 2018 for discussion). Their results indicate that the multisensory information of audio-visual speech may facilitate word processing analogously to the facilitation provided by word repetition.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, Basirat et al (2018) found that this repetition effect on the P200 interacted with multisensory context. For the initial word presentation, audio-visual words were associated with a smaller ERP than were the audio-only words, suggesting that the visual context facilitated lexical access (see Basirat et al, 2018 for discussion). Their results indicate that the multisensory information of audio-visual speech may facilitate word processing analogously to the facilitation provided by word repetition.…”
Section: Discussionmentioning
confidence: 85%
“…The P200 ERP component is known to be modulated by word repetition (e.g., Almeida & Poeppel, 2013). However, Basirat et al (2018) found that this repetition effect on the P200 interacted with multisensory context. For the initial word presentation, audio-visual words were associated with a smaller ERP than were the audio-only words, suggesting that the visual context facilitated lexical access (see Basirat et al, 2018 for discussion).…”
Section: Neurophysiological Processing Of Multisensory Speechmentioning
confidence: 90%
See 1 more Smart Citation
“…An increasing body of studies has explored the mechanisms underlying audiovisual integration of letters and speech sounds [7][8][9] and consistently demonstrated the superiority of audio-visual integration over processing letters and speech sounds separate [10,11]. For example, a magnetoencephalography (MEG) study showed enhanced brain activity predominantly in the right temporal-occipital-parietal junction and the left and right superior temporal sulci for audio-visual integration of phonemes and graphemes [12].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of studies has explored the mechanisms underlying audiovisual integration of letters and speech sounds [7][8][9] and consistently demonstrated the superiority of audio-visual integration over processing letters and speech sounds separate [10,11]. For example, a magnetoencephalography (MEG) study showed enhanced brain activity predominantly in the right temporal-occipital-parietal junction and the left and right superior temporal sulci for audio-visual integration of phonemes and graphemes [12].…”
Section: Introductionmentioning
confidence: 99%